(untitled) (Research, Society and Development, 2022)
Polycystic Ovary Syndrome is a complex and heterogeneous disorder that constitutes one of the endocrinological disorders that most affect women of reproductive age so that manifestations of its symptoms usually appear during adolescence. Still, specific studies on the health of women and girls are quite scarce, since in most societies they are harmed by discrimination based on sociocultural factors. Thus, this article proposes to analyze the most current literature available on the occurrence of PCOS in adolescents and its pharmacotherapy assuming that its diagnosis and treatment present particularities age related. The descriptors were used in combination “Polycystic Ovary Syndrome” AND “pharmacotherapy” AND “adolescents” in Portuguese and considering publications from the last five years (2017 to 2022). The search resulted in the selection of six articles in the databases of Google academic, Scientific Electronic Library Online (SCIELO) and Biblioteca Virtual em Saúde - BVS (with Medline and Lilacs) consistent with the inclusion and exclusion criteria defined first. The articles were discussed in two thematic categories: one addressing general features of PCOS in adolescents and the second focusing on pharmacotherapy and alternative treatments. It is noticed that there are still divergences regarding the diagnosis, however, the most recommended treatments are the use of contraceptives combined with insulin sensitizers, in addition to lifestyle changes adopting healthy habits.